At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

1/9 (2m - 16) = 1/3 (2m + 4)

Sagot :

Answer:

[tex]m=7\frac{5}{16}[/tex]

Step-by-step explanation:

[tex]\frac{1}{9}(2m - 16)=\frac{1}{3}(2m + 4)[/tex]

[tex]\frac{2}{9}m - 1\frac{7}{9} =\frac{2}{3}m+ 1\frac{1}{3}[/tex]

[tex]\frac{2}{9}m - 1\frac{7}{9} -1\frac{1}{3} =\frac{2}{3}m+ 1\frac{1}{3}-1\frac{1}{3}[/tex]

[tex]\frac{2}{9}m - 3\frac{1}{9} =\frac{2}{3}m[/tex]

[tex]\frac{2}{3}m-\frac{2}{9}m= \frac{2}{9}m -\frac{2}{9}m - 3\frac{1}{9}[/tex]

[tex]\frac{4}{9}m= - 3\frac{1}{9}[/tex]

[tex]\frac{4}{9}m/\frac{4}{9} = - 3\frac{1}{9}/\frac{4}{9}[/tex]

[tex]m=7\frac{5}{16}[/tex]